Hypoxia-Related Gene FUT11 Promotes Pancreatic Cancer Progression by Maintaining the Stability of PDK1 - Cao, Wenpeng; Zeng, Zhirui; Pan, Runsang; Wu, Hao; Zhang, Xiangyan; Chen, Hui; Nie, Yingjie; Yu, Zijiang; Lei, Shan (Frontiers in Oncology, 2021)
Background: Hypoxia participated in the occurrence and development of pancreatic cancer (PC). However, genes associated with hypoxia respond and their regulated mechanism in PC cells were unclear. The current research was aimed to illuminate the role and hypoxia regulated mechanism of fucosyltransferase 11 (FUT11) in the progression of PC. Methods: After predicting FUT11 as a key hypoxia associated gene in PC using bioinformatics analysis. The expression of FUT11 in PC using quantitative real-time fluorescent PCR, western blot and immunohistochemistry. The effects of FUT11 on PC cells proliferation and migration under normoxia and hypoxia were detected using Cell Counting Kit 8, 5-ethynyl-2’-deoxyuridine assay, colony formation assay and transwell assay. Spleen capsule injected liver metastasis and subcutaneously injected model were performed to confirm the effects of FUT11 in vivo. Furthermore, western blot, luciferase assay and immunoprecipitation were performed to explore the regulated relationship among FUT11, hypoxia-inducible factor 1α (HIF1α) and pyruvate dehydrogenase kinase 1 (PDK1) in PC. Results: FUT11 was markedly increased of PC cells in hypoxia, up-regulated in the PC clinical tissues, and predicted a poor outcome. Inhibition of FUT11 reduced PC cell growth and mobility of PC cells under normoxia and hypoxia conditions in vitro, and growth and mobility in vivo. FUT11 bind with PDK1 and regulated the expression PDK1 under normoxia and hypoxia. FUT11 knockdown significantly increased the degradation rate of PDK1 under hypoxia, while treatment with MG132 can relieve the degradation of PDK1 induced by FUT11 knockdown. Overexpression of PDK1 in PC cells under hypoxia conditions reversed the suppressiv impacts of FUT11 knockdown on PC cell growth and mobility. In addition, HIF1α bound to the enhancer of FUT11 and increased its expression, as well as co-expressing with FUT11 in PC tissues. Furthermore, overexpress of FUT11 partially rescued the suppressiv effects of HIF1α knockdown on PC cell growth and mobility in hypoxia conditions. Conclusion: Our data further implicate that hypoxia-induced FUT11 in PC contributes to proliferation and metastasis by maintaining the stability of PDK1, and suggest FUT11 maybe a novel and effective target for treatment of pancreatic cancer.